Molecular mechanism of ferroptosis and its role in the occurrence and treatment of diabetes - Du, Guanghui; Zhang, Qi; Huang, Xiaobo; Wang, Yi (Frontiers in Genetics, 2022)
Ferroptosis is an iron-dependent programmed cell death, which is different from apoptosis, necrosis and autophagy. The main mechanism of iron death is that, under the action of divalent iron or ester oxygenase, the unsaturated fatty acids which are highly expressed on the cell membrane are catalyzed to produce lipid peroxidation, thus inducing cell death. In addition, the expression of antioxidant system (glutathione (GSH) and glutathione peroxidase 4(GPX4)) was decreased. Iron death plays an important role in the development of diabetes mellitus and its complications. In this article, we reviewed the role of the molecular mechanism of iron death in the development of diabetes mellitus and its complications. We also summarized the emerging questions in this particular area of research, some of which remain unanswered. Overall, this is a comprehensive review focusing on ferroptosis mediated diabetes and providing novel insight in the treatment of diabetes from the ferroptosis perspective.